Complexity and distributive fairness interact in affecting compliance behavior - Charles Bellemare; Marvin Deversi; Florian Englmaier (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Filing income tax returns or insurance claims often requires that individuals comply with complex rules to meet their obligations. We present evidence from a laboratory tax experiment suggesting that the effects of complexity on compliance are intrinsically linked to distributive fairness. We find that compliance remains largely unaffected by complexity when income taxes are distributed to a morally justified charity. Conversely, complexity significantly amplifies non-compliance when income taxes appear wasted as they are distributed to a morally dubious charity. Our data further suggest that this non-compliance pattern is facilitated through the ambiguity that evolves from mostly unstrategic filing mistakes.
Keywords: C91; D01; D91; H26; 330; complexity; compliance; distributive fairness; experiment